A comparison of oil-water separation by gravity and electrolysis separation process. Issue 2 (22nd January 2021) - Elhemmali, Alaaeddin; Anwar, Shams; Zhang, Yahui; Shirokoff, John
ABSTRACT: This study investigates the performance of oil-water separation experimentally using two methods: gravity separation, and electrolysis separation. A factorial design experiment was conducted for gravity separation using a five-variable experimental plan where the factors are as follows: water flow rate, oil flow rate, temperature, number of compartments (2) and (1), and type of separator inlet deflector plate and elbow. The electrolysis separation was conducted using one factor at a time method. It was found that increasing temperature, voltage, and (NaCl) salt increases the performance of oil-water separation, however increasing the pH or volumetric oil to water ratio acts adversely.